Contemporary Party-Union Relations in Canada - Savage, Larry (Labor Studies Journal, 2010)
The longstanding political alliance between the Canadian labor movement and the New Democratic Party (NDP) has experienced new stresses in recent years. Whereas the NDP was widely considered the political arm of the labor movement during the Keynesian post-war period, under neoliberalism, the relationship between most unions and the NDP has become more tactical and less cohesive. This article surveys contemporary party-union relationships in Canada, at both the federal and provincial levels, with a view to demonstrating that weakening party-union relations are rooted in larger macro-economic and political transformations and are shaped by factors related to region and language.
Keywords: Canada; New Democratic Party; Quebec; elections